2005
DOI: 10.1097/01.hjh.0000163157.14493.c7
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve sclerosis is associated with preclinical cardiovascular disease in hypertensive adults: the Hypertension Genetic Epidemiology Network study

Abstract: In a population-based sample of hypertensive adults, AVS was prevalent (9.4%) and associated with a proatherogenic clinical profile and abnormal left ventricular geometry and filling, increased left atrial size and mitral annular calcification, which may contribute to the adverse prognosis associated with AVS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 47 publications
0
9
2
3
Order By: Relevance
“…This fact has been already demonstrated in necropsy 1 and population studies, which have shown the occurrence of calcium deposits in the cardiovascular system of individuals with atherosclerotic disease. [2][3][4] TTE is a practical tool to assess cardiac calcium and its efficacy is comparable to that of angiotomography, as demonstrated in the Heinz Nixdorf Recall study, published in JAMA in 2010. 5 There is no standardization in regards to the quantification of cardiac calcium on TTE, and the present study used the Gaibazzi 6 score for this purpose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact has been already demonstrated in necropsy 1 and population studies, which have shown the occurrence of calcium deposits in the cardiovascular system of individuals with atherosclerotic disease. [2][3][4] TTE is a practical tool to assess cardiac calcium and its efficacy is comparable to that of angiotomography, as demonstrated in the Heinz Nixdorf Recall study, published in JAMA in 2010. 5 There is no standardization in regards to the quantification of cardiac calcium on TTE, and the present study used the Gaibazzi 6 score for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Similar to computed tomography (CT), bidimensional transthoracic echocardiography (TTE) is capable of detecting cardiac calcium deposits, and is a portable, noninvasive, nonradioactive, and low-cost method. 5 Coronary angiotomography is known to predict individual risk of coronary events, evaluating the calcium score of the coronary arteries and the semiquantitative scores of valvular calcium.…”
Section: Introductionmentioning
confidence: 99%
“…A single experienced reader (NBS), blinded to clinical history, physical examination, laboratory data, and outcome variables, interpreted all echocardiograms for aortic valve morphologic characteristics, sclerosis, and stenosis. Similar to other studies, 3,4 we defined aortic sclerosis as the presence of focal areas of aortic valve leaflet thickening and/or increased echogenicity with preserved leaflet mobility and a peak Doppler velocity across the aortic valve of <2.0 m/s. We found good intraobserver agreement for aortic valve morphologic characteristics during an intraobserver reliability analysis of 31 participants (κ = 0.62, 95% confidence interval [CI] 0.36 to 0.87).…”
Section: Methodsmentioning
confidence: 99%
“…3 Our results show that the presence of aortic sclerosis is a powerful predictor of MI events and adds further credence to the hypothesis that aortic sclerosis is a marker of atherosclerotic burden. Because patients with aortic sclerosis have more cardiac calcium and worse left ventricular function than those without aortic sclerosis, 4,7,17 it is important to account for echocardiographic differences when examining the association of aortic sclerosis with CV outcomes. We found that aortic sclerosis predicts MI even after adjustment for echocardiographic variables, including mitral annular calcium, exercise-induced ischemia, and left ventricular diastolic function.…”
Section: Discussionmentioning
confidence: 99%
“…These include inflammation [4,5], lipoprotein abnormalities [6] and endothelial dysfunction [7]. Furthermore, both large population-based studies [1] and subgroup analyses of cohorts of hypertensive patients [8,9] have shown that subjects with aortic sclerosis have increased LV wall thickness. In theory, coexistence of LV hypertrophy with aortic sclerosis may contribute to the increase in cardiovascular risk and therefore it is important to understand the mechanism for the increase in LV mass.…”
Section: Introductionmentioning
confidence: 99%